ANALISIS EFEKTIVITAS PEMBELAJARAN FISIKA MENGGUNAKAN MODUL FLUIDA STATIS BANGUNAN KERAMBA IKAN PADA SISWA SMA NEGERI 5 JEMBER - Sri Septi Dyah Pratiwi; Trapsilo Prihandono; Lailatul Nuraini; Abdul Rozak (JURNAL PEMBELAJARAN FISIKA, 2022)
Analysis of the effectiveness of learning using static fluid modules in fish cage buildings is carried out by collecting data through the results of the students' Pre-test and Post-test which then determines the level of effectiveness through the N-Gain test. This study has a goal, namely to find out how the effectiveness of learning by using static fluid modules in fish cage buildings for students of SMA Negeri 5 Jember. The type of research used is an experiment, with a pretest-posttest control group design. Respondents in the study were students of class XI MIPA 2 as the control class and students of class XI MIPA 3 as the experimental class. The research results obtained in the experimental class with learning using the static fluid module of fish cage buildings obtained an N-Gain value of 69.4% in the "Moderate" category with an effectiveness interpretation of "Effective enough", while the results for the control class obtained an N-Gain value of 36 % category "Moderate" with the interpretation "Not Effective". The conclusions that can be obtained in this study are based on hypothesis testing, so there is a significant effectiveness of learning using static fluid modules in fish cage buildings.